Improving Students’ Arabic Vocabulary Acquisition through the Use of Picture Media - Nurul Ainiyatus Sholihah; Saefullah Azhari; Nurul Istiqomah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to describe the use of picture media in improving Arabic vocabulary (mufrodat) comprehension among seventh-grade students at MTs Taswirul Afkar Surabaya. Learning Arabic vocabulary often poses challenges for students because Arabic words tend to be abstract and require a high level of memorization. Therefore, appropriate learning strategies are needed to help students understand vocabulary in a more concrete manner. Picture media are used as instructional tools to connect Arabic vocabulary with visual representations that are relevant to students’ daily lives. This study employed a qualitative approach with a field research design. The research subjects consisted of seventh-grade students and an Arabic language teacher at MTs Taswirul Afkar Surabaya. Data were collected through observation, interviews, and documentation to obtain an in-depth understanding of the learning process and students’ responses to the use of picture media. The collected data were analyzed using descriptive qualitative analysis, with data validity ensured through the criteria of credibility, transferability, dependability, and confirmability. The findings indicate that the use of picture media helps students better understand and remember Arabic vocabulary, increases learning interest, and encourages active student participation during the Arabic learning process. Therefore, picture media can be considered an alternative instructional strategy for teaching Arabic vocabulary that is contextual and appropriate to the characteristics of students at the madrasah tsanawiyah level.